Polski emigracyjny ruch wydawniczo-księgarski w Lipsku w latach 1830–1918 - Agnieszka Łukomska-Kryger (Biblioteka)
This article attempts to summarize and systematize available data on Polish emigre publishing, printing and book trade in Leipzig. The chronological span covers the years 1830–1918, i.e., shortly before the outbreak of the November insurrection, the following years of the emigration of political elites from Poland (the socalled Great Emigration) until the times when Poland regained its independence in 1918.